Web-Based Learning Implementation to Improve Students' Learning Outcomes on Understand Evaluating the Public Policies’ Impact Material during the Covid-19 Pandemic - Susilawati, Evi; Khaira, Imamul (Nusantara Science and Technology Proceedings, 2021)
The Covid-19 Pandemic (CoronaVirus Disease-19) caused the Government of the Republic of Indonesia to implement various policies to tackle the spread of Covid-19 so that those policies’ impacts need to be evaluated. This activity of learning to topic evaluate the impact of public policies during the Covid-19 pandemic was carried out in the Public Policy course. This research activity uses a web-based learning strategy. Based on these web-based learning activities, this study aims: (1) to see web-based learning applications on the evaluation material for the impact of public policies during Covid-19, and (2) to see the increase in students' abilities in understanding the material for evaluating the impact of public policies during the Covid-19 pandemic. This research is Classroom Action Research (CAR). The research subjects subject to action were students of semester VII of the Pancasila and Civic Education study program, Faculty of Teacher Training and Education of the Islamic University of North Sumatra in the 2020/2021 academic year. The data analysis in this study used qualitative and quantitative descriptive techniques. The validity of the data in this study was carried out using observation sheets and student learning achievements tests on the evaluation material for the impact of Public Policy during the Covid-19 pandemic. The results of this study indicate that there is an increase in the learning outcomes of students to understand the material for evaluating the impact of public policies during the Covid-19 pandemic using web-based learning.